THE SYMBOLIC MEANING OF THE GREAT FLYING PERFORMANCE AT THE LONG MULUD CEREMONY AT THE TEAK PANGGUNG, TAKTAKAN, SERANG CITY, BANTEN PROVINCE - Wiwin Purwanti (Universitas Pendidikan Indonesia, 2022)
Based on the data that is managed in the study, the involvement of Art Terebang Gede on Panjang Mulud a ceremony in the Panggung Jati teak, has an important role. Therefore, art Terebang Gede in these activities are integrated in the social structure that involves the community to jointly interpret its symbols, so that through these symbols can be found meaning, acceptable and mutually agreed anyway. Through symbolizing the birth of Prophet Muhammad Solallohu Alaihi Wasalam, strung in the form of Panjang Mulud ceremony and expressed in musical activities, has been able to raise the collective consciousness. So through these symbols can influence and shape social life. Thus, the existence of the art Terebang Gede in a ceremony in the Panjang Mulud identity and not merely a form of aesthetic representation